The racial discrimination of white and black As seen in benjamin zephaniah’s poems - Tegar Risadi Chalid; Feby Meuthia Yusuf (Fakultas Sastra Universitas Ekasakti, 2017)
The problem in this thesis is the racial discrimination from white community against black community that was their former slave in the past, the author analyzes three poems by Zephaniah based on the issue of racial discrimination. Poem represents the poet’s feeling about the social phenomena that surrounds him, and these poems are also the form of protest against racial discrimination. The purpose of this study is to analyze the treatment from white communities against black communities that consider that their race to be superior compared to their former slaves. The manifestation of racial discrimination can be seen from the attitude of prejudice, insulting words and remarks, and the acts of oppression on black community. In this writing, library research is taken as the method of data collection. As for the method of data analysis, the author performs systematic procedures by understanding of the poem, the theme of racial discrimination, and also the theory of psychology. Data collection technique uses qualitative techniques in finding the data in form of explanation on the phenomenon that occurs. In the technique of data analysis, the writer uses genetic structuralism techniques by analyzing the oppression of black society in Zephaniah’s poems through psychology theory. The findings in this thesis are: 1) in the poem of The Race Industry, white society always oppresses black society so that they have to work hard but do not get the result that they deserves, 2) in poem We Refugee, white society always have prejudice against black people because of their skin color and not because of their actions, 3) in Dis Poetry, white community always says provocative words and remarks to offend black people.